2013
DOI: 10.5653/cerm.2013.40.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genistein administration on the recovery of spermatogenesis in the busulfan-treated rat testis

Abstract: ObjectiveImpairment of spermatogenesis has been identified as an inevitable side effect of cancer treatment. Although estrogen treatment stimulates spermatogenic recovery from the impaired spermatogenesis by suppressing the intra-testicular testosterone (ITT) level, side effects of estrogen are still major impediments to its clinical application in humans. Soybeans are rich in genistein, which is a phytoestrogen that binds to estrogen receptors and has an estrogenic effect. We investigated the effects of genis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…In current investigation, 1∼300 mg/kg β-carotene was used with or without busulfan for dosing mice, we found that busulfan (single dose 40 mg/kg BW at 3 weeks of age) resulted in azoospermia in mice during adulthood (8 weeks of age). The result was consistent with lots of previous reports ( Chi et al, 2013 ; Jung et al, 2015 ; Liu et al, 2019 ). Moreover, β-carotene increased sperm concentration and motility after busulfan treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In current investigation, 1∼300 mg/kg β-carotene was used with or without busulfan for dosing mice, we found that busulfan (single dose 40 mg/kg BW at 3 weeks of age) resulted in azoospermia in mice during adulthood (8 weeks of age). The result was consistent with lots of previous reports ( Chi et al, 2013 ; Jung et al, 2015 ; Liu et al, 2019 ). Moreover, β-carotene increased sperm concentration and motility after busulfan treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Many investigations have attempted to improve spermatogenesis and male fertility using a busulfan treated animal model. Busulfan can cause azoospermia by destroying testicular germ cells and increasing sperm abnormalities ( Chi et al, 2013 ; Jung et al, 2015 ; Liu et al, 2019 ). It has been reported that molybdenum (Mo) rescued mouse spermatogenesis by the improvement of male germ cell development s, and maintaining of blood hormone levels (testosterone, estradiol, and luteinizing hormone) ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gynecomastia and cardiovascular problems are secondary effects related to E 2 treatment and represent the major impediment to clinical application. Recently, it has been suggested that the phytoestrogen genistein may be a true substitute for E 2 ( 135 ).…”
Section: Estrogens and Sperm Qualitymentioning
confidence: 99%
“…In 2014, Jones et al, [ 26 ] demonstrated that simultaneous gestational exposure to GEN and DEHP induced long-term alterations in testis development and function. Besides, GEN has also been reported to mitigate radiation-induced testicular damage in male C3H/HeN mice with 200 mg/kg body weight administration [ 27 ] as well as recover spermatogenesis in the busulfan-treated rat testis orally daily at a dose of either 50 or 100 mg/kg [ 28 ]. In our present study, we found that ICR mice orally at a dose of 5 mg/kg/day for 35 days could induce abnormal spermatogenesis to some extent, mainly on mice VAP, VSL and VCL.…”
Section: Discussionmentioning
confidence: 99%